Otolith-Based Chronology of Brazilian Shellmounds. Issue 2 (25th January 2019) - Carvalho, Carla; Oliveira, Fabiana; Macario, Kita; Lima, Tania; Chanca, Ingrid; Alves, Eduardo Q; Bertucci, Thayse; Aguilera, Orangel
ABSTRACT: The radiocarbon ( 14 C) chronology of hunter-fisher-gatherers' archaeological settlements along the Brazilian coast is usually based on mollusk shells, charcoal from hearths, and eventually human bones. However, fish otoliths are found in several archaeological contexts and may represent a reliable option as a chronological record. In this work, we compare the 14 C dates of whitemouth croakers ( Micropogonias furnieri ) otoliths with dates obtained from other materials (shell and charcoal), collected from shellmounds on the coast of Rio de Janeiro, with the aim of improving the accuracy in the 14 C dating of Brazilian shellmounds, strengthening the comprehension of the native populations' occupational trends and the coeval palaeoceanographic context. Based on x-ray diffraction results for archaeological otoliths, their geochemical composition indicates minimal diagenesis effect over time even under burial conditions in the studied sites. The comparison between otolith dates and dates obtained from other proxies revealed similar results but with decreased deviations in otolith dates in all of the studied sites.